Exploring mania-associated white matter injury by comparison with multiple sclerosis: a diffusion tensor imaging study. (30th November 2018) - Piaggio, Niccolò; Schiavi, Simona; Martino, Matteo; Bommarito, Giulia; Inglese, Matilde; Magioncalda, Paola
Highlights: Both mania and multiple sclerosis show white matter changes in the corpus callosum. Mania shows a greater degree of alterations in the anterior part of corpus callosum. Multiple sclerosis shows greater alterations in the posterior part of this tract. These disorders show common white matter alterations with divergent spatial pattern. Bipolar disorder and multiple sclerosis might share some pathophysiological features. Abstract: Bipolar disorder (BD), especially in its active phases, has shown some neuroimaging and immunological similarities with multiple sclerosis (MS). The objective of this study was to compare white matter (WM) alterations in BD patients in manic phase (M-BD) and MS patients at early stage of disease and with low lesion burden. We compared diffusion tensor imaging (DTI)-derived fractional anisotropy (FA), mean diffusivity (MD) and radial diffusivity (RD) in a priori selected WM regions (i.e., corpus callosum and cingulum) betwixt 23 M-BD, 23 MS patients and 46 healthy controls. Both M-BD and MS showed WM changes in the corpus callosum, which, however, showed a greater impairment in MS patients. However, considering the different sub-regions of corpus callosum separately (i.e., genu, body, splenium), M-BD and MS presented an opposite pattern in spatial distribution of WM microstructure alterations, with a greater impairment in the anterior region in M-BD and in the posterior region in MS. Common features as well as divergent patterns in DTI changes are detected in M-BD and early MS, prompting a deeper investigation of analogies and differences in WM and immunological alterations of these disorders.